The Middle to Late Triassic of Central Saudi Arabia with emphasis on the Jilh Formation. Part II: sequence stratigraphy, depositional and structural history, correlations and paleogeography - Le Nindre, Yves-Michel; Davies, Roger Brett; Issautier, Benoit; Krystyn, Leopold; Vaslet, Denis; Vrielynck, Bruno; Memesh, Abdullah (Comptes Rendus. Géoscience)
New biostratigraphic data reported by Le Nindre et al. (2023 – this volume) improve the sequence stratigraphic understanding of the Middle–Late Triassic mixed carbonate-silicilclastic Jilh Formation and overlying siliciclastic Minjur Formation at outcrop in Central Saudi Arabia. The Anisian Tr40, Ladinian Tr50, Julian Tr60, Tuvalian Tr70 and Alaunian Tr80 MFS are all identified and their ages discussed. A major Carnian–Norian hiatus (Tr80 SB) approximates to but notably cuts across the mapped Jilh–Minjur Formation boundary. A younger Late Norian–Rhaetian transgression (Tr90 MFS?) is also identified. All of these major transgressive–regressive sequences and hiatuses can be identified with confidence and correlated at the regional scale with time-equivalent carbonates. The ages of subsurface lithostratigraphic units identified elsewhere across the Arabian Plate, notably the “Jilh, Sefidar and Marker Dolomites”, “Jilh Evaporite” (sometimes “Carnian Salinity Crisis”) and the incertae sedis Baluti Formation, and their equivalence in the Saudi Arabian outcrops, are assessed in the light of these results. The presence of significant siliciclastics at the base of the Carnian stratigraphy (“Julian Clastic Event”) is also discussed.Ladinian conodont faunas belonging to the Sephardic Province (Iberia, North Africa) and associated vertebrate faunas confirm transgression from the north. Similar conclusions are drawn for the Carnian and Norian transgressions.The improved geochronologic understanding enabled a reconstruction of the structural phases of the Jilh geohistory in four steps from Anisian to Norian, showing the relationships of retrogradation–progradation processes and tectonic pulses to hiatuses and periods of erosion. A synthetic sequence stratigraphy is proposed.